Autophagy regulates fatty acid availability for oxidative phosphorylation through mitochondria-endoplasmic reticulum contact sites - Claudie Bosc; Nicolas Broin; Marjorie Fanjul; Estelle Saland; Thomas Farge; Charly Courdy; Aurélie Batut; Rawand Masoud; Clément Larrue; Sarah Skuli; Nicolas Espagnolle; Jean-Christophe Pagès; et al. (Nature Communications, 2020)
How autophagy supports tumor cell metabolism is not fully clear. Here, the authors show that autophagy regulates lipid availability to support mitochondrial oxidative metabolism through mitochondria-endoplasmic reticulum contact sites, necessary for cell proliferation in AML.